Carbetocin versus Oxytocin in the Prevention of Postpartum Haemorrhage after Caesarean Section (Bangladesh Journal of Obstetrics & Gynaecology, 2022)
Background: postpartum haemorrhage is one of the major contributors to maternal mortality and morbidity worldwide. There are many pharmacological options for the management of postpartum hemorrhage, oxytocin being the first line choice of treatment.Carbetocin, a long acting oxytocin agonist, appears to be a promising agent for the prevention of PPH. This comparative study was between Carbetocin Versus Oxytocin for the Prevention of Postpartum Haemorrhage in Caesarean SectionObjective: To determine the safety and effectiveness of carbetocin and oxytocin for the prevention of post-partum haemorrhage in caesarean section.Methods: Randomized controlled clinical trial was done in the department of Obstetrics and Gynaecology of Sir Salimullah Medical College Mitford Hospital, Dhaka, between February to July 2015. Study population were 64 pregnant women admitted for delivery and underwent caesarean section, who were randomly selected. Women in the intervention group (group I) received injection carbetocin a bolus of 100 mgm IV; women in the standard treatment group (group II) received 10 IU of oxytocin in IV.Both administered immediately after chiidbirth.This trial was registered in SSMC MH with reference no-SSMC/2014/76.Result: Difference of mean age,mean gestational age and indication of C/S were not statistically significant between two groups.Regarding haemodynamic effect,both drugs were almost similar.There was no significant difference in per-operetive blood loss,uterine tone, level of uterine fundus, urine output in urobag and hemoglobin level. Need for additional oxytocics required 0(0.0%) vs 5(16.7%) patients in group I and group II respectively and was found statistically significant.Blood transfusion needed was 0(0.0%) vs 3(10.0%) patients and primary PPH 0(0.0%) vs 3(9.4%),though both were not statistically significant. No significant difference regarding side effects and total expense was found.Conclusion: Administration of single bolus dose of carbetocin (100 μgIV) after delivery of the baby in caesarean section immediately reduces the need for additional oxytocics, occurrence of primary PPH and further blood transfusion. Side effects are mild and similar in both the groups.Bangladesh J Obstet Gynaecol, 2020; Vol. 35(2): 63-67